Compliance with Food Safety Standards among Cracker Producers in Sidoarjo: Kepatuhan terhadap Standar Keamanan Pangan di Kalangan Produsen Kerupuk di Sidoarjo - Dewi Kusuma Nada (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Food safety governance is essential to protect public health, particularly in widely consumed traditional foods produced by small and medium enterprises. Specific Background The cracker industry in Sidoarjo Regency represents a major local economic sector dominated by micro, small, and medium producers whose production practices vary in relation to regulatory requirements. Knowledge Gap Previous studies have largely examined hygiene or general manufacturing practices, with limited empirical analysis focusing specifically on producer compliance with food safety standards within a regional industrial cluster. Aims This study investigates the level of compliance among cracker producers in Sidoarjo with national food safety regulations and identifies key barriers faced by small and medium enterprises. Results Survey findings from 20 producers reveal high regulatory awareness (95%), substantial certification ownership (80%), but inconsistent application of safe raw materials (60%), alongside challenges including production costs, limited access to compliant inputs, and insufficient training and supervision. Novelty The research provides localized empirical evidence linking regulatory awareness, certification status, production practices, and operational constraints within a specific traditional food sector. Implications Strengthening enforcement mechanisms, expanding producer education, and providing technical and financial assistance are necessary to ensure safer food production and stronger consumer protection within small-scale food industries. Highlights: Regulatory awareness among producers is widespread, yet operational practices remain uneven. Certification ownership does not guarantee consistent use of safe ingredients. Financial constraints and limited training hinder adherence to required standards. Keywords:Food Safety; Producer Compliance; Small and Medium Enterprises; Cracker Industry; Consumer Protection